The Effect of Bifidobacterium Probiotic on Heat Shock Protein-70 Expression and Osteoclast Number during Orthodontic Tooth Movement in Rats (Rattus novergicus) - Ari Triwardhani, - (Asociacion Academica de Ciencias Farmaceuticas de Antofagasta (ASOCIFA), 2021)
Heat shock protein (HSP)-70 expressed in the fibroblast of periodontal ligament after orthodontic tooth movement (OTM) was applied. Bifidobacterium probiotics regulate the number of osteoclasts through controlling the inflammation via Nuclear Factor Kappa Beta (NFKB) and increased Cytoprotection by HSP induction. This study aimed to examine the effect of Bifidobacterium probiotic on HSP-70 expression and osteoclast number during OTM in the compression side of Wistar rats (Rattus novergicus). This research was a true experimental study which used post-test only group design. 42-healthy-Wistar rats (R. novergicus) were blind randomly divided into 6 groups; K1: OTM for 3 days; K2: OTM for 7 days; K3: OTM for 14 days; KP1: OTM and administration of Bifidobacterium probiotic for 3 days; KP2: OTM and administration of Bifidobacterium probiotic for 7 days; KP3: OTM and administration of Bifidobacterium probiotic for 14 days. OTM model was made by installed closed-coil spring with 10g/mm2 force. Bifidobacterium probiotic was orally administered with 10mL/day by means of oral gavage at 1.5 x 108 CFU/mL dose every day. Immunohistochemical analyses were performed in all study groups. One-way ANOVA and LSD test (p<0.05) were performed to compare between groups. The highest HSP-70 expression was discovered in K3 control group and the greatest osteoclast number was found in KP1 control group. The lowest HSP-70 expression and osteoclast number were found in KP3 group with significant between groups. Bifidobacterium probiotic decreased the expression of HSP-70 and osteoclast number during the orthodontic tooth movement in 14 days in the compression side.